The relationship between body mass index and blood sugar levels among menopausal women - Manao, Oktoriadi; Lubis, Yolanda Eliza Putri; Nasution, Masdalena (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Decreased estrogen levels during menopause are often associated with various health problems, one of which is carbohydrate metabolism disorders characterized by changes in blood sugar levels. The purpose of this study was to analyze the relationship between body mass index (BMI) and blood sugar levels in menopausal women. This study is an analytic descriptive study with a cross-sectional design. The research sample involved all women aged 40-60 years who met the inclusion criteria. The results showed that most of the respondents (75%) were included in the late elderly category (age >56 years). Based on BMI, the majority of respondents (35%) were categorized as obesity I. Additionally, 51.7% of respondents had high blood glucose levels. Statistical analysis revealed a significant relationship between age status and blood glucose levels (p-value = 0.000). Similarly, there was a significant relationship between BMI and blood glucose levels (p-value = 0.026). These results indicate that age and obesity are factors associated with increased blood sugar levels in menopausal women.